Semiotic Analysis of the Film Dirty Vote in the 2024 Election - Amin, Amin; Habib, Mohd. Nadzrizal; Putri, Melani Andika; Poetri, Maharanny Setiawan (Peneliti.net, 2024)
This research analyzes the documentary “Dirty Vote” using Ferdinand de Saussure's semiotic analysis to identify and interpret the signs and symbols used in the film. The film, which was released ahead of the 2024 General Election, raises the issue of fraud in Indonesia's electoral process. The semiotic analysis shows that the signs in the film represent complex political strategies and manipulations, including the use of the chess game symbol to illustrate careful planning and the term